About Quantum Metrology - Asgarov, K.A.; Yuzbashov, E.R. (Herald of Azerbaijan Engineering Academy, 2024)
Quantum metrology, being a branch of modern metrology, is a study that provides highresolution and very sensitive measurement of physical parameters by explaining the properties of physical systems in terms of quantum theory. By developing new measurement methods, this field demonstrates higher accuracy than the same measurements performed in a classical framework.